High-twist-pervaded electrochemical yarn muscles with ultralarge and fast contractile actuations. Issue 11 (6th October 2020) - Wang, Yulian; Qiao, Jian; Wu, Kunjie; Yang, Wei; Ren, Ming; Dong, Lizhong; Zhou, Yurong; Wu, Yulong; Wang, Xiaona; Yong, Zhenzhong; Di, Jiangtao; Li, Qingwen
Abstract : Carbon nanotube yarn muscles with a high-twist-pervaded and hierarchical structure show ultra-large and fast contractile actuations when driven by electrochemical ion injection. Abstract : Artificial yarn muscles, behaving like real muscles but providing higher energy output, have attracted considerable interest recently. However, yarn muscles driven by low-voltage electrochemical ion injection still suffer from low contraction and slow responses. Herein, an electrochemical yarn muscle with ultralarge and fast contractile actuations was prepared by twisting and coiling a group of s-spun carbon nanotube (CNT) yarns that have a layered inner structure. When electrochemically driven at 3.0 V, the yarn muscle generated 62.4% contraction in 5 s while lifting a heavy weight 10 000 times the mass of the muscle, outperforming normal yarns containing the same amount of CNTs and the literature results for electrochemical yarn muscles. A linear dependence of the contraction on the voltage was observed, which is of great importance for muscle control. Moreover, the yarn muscle showed high cycling stability with >95% contraction retention after 4500 running cycles. The high actuation performance was attributed to the existence of the highly twisted structure pervading the whole yarns for large effective actuation volume and the presence of gaps at hierarchical levels that facilitate ion injection. Considering the low driving voltages, programmable contractions, and high energy output, the present yarn muscles can help the development of soft robots and artificial limbs.